Re-evaluation of the morphology of the monotypic genera Lycastonereis Rao, 1981 and Ganganereis Misra, 1999 (Annelida, Phyllodocida, Nereididae) - Conde-Vela, Víctor M. (Zootaxa, 2019)
The monotypic genera Lycastonereis Rao, 1981 and Ganganereis Misra, 1999, and their respective species L. indica Rao, 1981 and G. sootai Misra, 1999, have unique morphological traits, and are only known from India and nearby countries. Lycastonereis is diagnosed by having three pairs of anterior cirri and biramous parapodia, whereas for Ganganereis the pharynx has partially sclerotized papillae arranged in a semi-continuous row in the maxillary ring, and chaetae include only spinigers throughout the body. The morphology of these species is not adequately understood as shown by their exclusion in phylogenetic analyses, and therefore an additional morphological evaluation is needed. The re-evaluation of the genera is based upon three specimens of L. indica and the original description of G. sootai. It is shown that L. indica has rounded papillae present in both maxillary and oral rings (not restricted to the oral ring), and in all areas except area V, and neuroacicular ligules are bilobed (not the postchaetal lobes). In addition, G. sootai is morphological similar to species of Paraleonnates Khlebovich & Wu, 1962, mainly in the arrangement and kind of structures of the pharynx, parapodial morphology, and chaetae; therefore, G. sootai is transferred to Paraleonnates, and Ganganereis is regarded as a junior synonym of Paraleonnates. A key to species of Paraleonnates is included.